(3efM Pi GddH GdSQM Hjf ahGFO GddH hGdTQMs - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG ,J (B1003 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi efM PG GddH GdhUhd Edi dH GdCUhd ef GdehMOjf GdCUdjjf ef Ydei Gdabg hGdOjf s
(3BNQgG (B:s
(3dGSGZ GdGYJHGQ bWQ GdbdH YeG dGjNai ef GdPi jXgQ di Cf gPG s
(3Vef eLehY , JQJjHgG (B: (3GdMGOi YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B235 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B133s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs